Atrial arrhythmias following lung transplant: a single pediatric center experience - Sill, Jordan; Baskar, Shankar; Zang, Huaiyu; Spar, David; Iliopoulos, Ilias; Morales, David L. S.; Hayes, Don; Koh, Wonshill (Frontiers in Pediatrics, 2023)
Background: Outcomes after lung transplant (LTx) in children have slowly improved. Although atrial arrhythmia (AA) is a common and adverse complication following LTx among adults, there is limited data on pediatric recipients. We detail our pediatric single-center experience while providing further insights on occurrence and management of AA following LTx. Methods: A retrospective analysis of LTx recipients at a pediatric LTx program from 2014 to 2022 was performed. We investigated timing of occurrence and management of AA following LTx, and its effect on post-LTx outcome. Results: Three out of nineteen (15%) pediatric LTx recipients developed AA. The timing of occurrence was 9-10 days following LTx. Those patients in the older age group (age >12 years old) were the only ones who developed AA. Developing AA did not have a negative effect on hospital stay duration or short-term mortality. All LTx recipients with AA were discharged home on therapy that was discontinued at 6 months for those who was on mono-therapy without recurrence of AA. Conclusions: AA is an early post-operative complication in older children and younger adults undergoing LTx at a pediatric center. Early recognition and aggressive management can mitigate any morbidity or mortality. Future investigations should explore factors that place this population at risk for AA in order to prevent this complication post-operatively.